Formation of effective mechanisms of organizational and economic ensuring the public administration of development of transport infrastructure - Lileiev , Mykyta (Global Prosperity, 2023)
The analysis and substantiation of theoretical and practical provisions regarding the formation of effective mechanisms of organizational and economic support of the state management of the construction and development of transport infrastructure in Ukraine was carried out. It was revealed that when developing infrastructure, it is necessary to operate existing facilities more efficiently and reduce the construction of new transport infrastructure facilities. To achieve this task, government authorities need to develop long-term intersectoral programs taking into account a technical analysis of the existing infrastructure, as well as apply various government mechanisms that stimulate more efficient use of transport infrastructure. According to established international practice, the system of financing infrastructure projects is provided through investment companies, investment banks and insurance companies, special projects for foreign direct investment, financial information agencies, rating agencies, and investor clubs. In the context of using public-private partnership approaches to solve these problems, the experience of implementing an infrastructure development model, in which various models of support for the infrastructure sector were used: American, British, French, providing for direct state regulation of infrastructure projects, deserves attention. The result is a public-private partnership model with financial leadership, in which the leading role in the management of a special project company is played by investment banks, which are responsible for the tender process and can provide credit to the company implementing infrastructure projects.Since the controlling stake in the company belongs to banks, the decision on the conditions for the participation of economic entities in the project, control over their implementation, as well as the fulfillment of financial obligations are ensured by the above-mentioned banks. By concentrating the implementation of the project under the unified control of the investment bank and its active participation in the project, transaction costs are reduced due to more rapid financing and a more optimal redistribution of financial flows.